A study on the antibacterial and antifungal properties of Persicaria odorata leaves against pathogenic bacteria and fungi - Muhd Ridzuan bin Pauzi (Kulliyyah of Medicine, International Islamic University Malaysia, 2014)
Persicuria odorata is a common plant and well known locally as ··daun kesum"' that is usually used in culinary and have various medicinal properties. This study was conducted to investigate the antimicrobial activitv and the chemical constituents of the ~ ~ most active extract. The leaves were extracted using n-hexane. dichloromethane and methanol consecutively. A non-consecutive extraction using 11ater was also performed to get another type of polar extract. All extracts were tested against eight bacteria which included Gram-positive and Gram-negative bacteria as well as one fungus species. Both standard ATCC and wild type strains microorganisms were used in this study. The antimicrobial activities of the extracts were assessed using disc diffusion method in parallel with control antibiotics and antifungal. The most active extract could be determined from the method and then. it was evaluated quantitatively using broth microdilution assay to assess the minimum concentration required to inhibit the microorganism gro111h. Gas chromatography- iVIass (GC -MS) Spectroscopy analysis was used to analyze the chemical constituent of the most active extract. The outcomes of this study showed that n-hexane extract was the most active against ATCC strains of Staphylococcus aurem (29.3 mm ±0.57) (p<0.005), S. epidermidis (32.6 mm ± 152) (p<0.005). S. pneumoniae ( 11.3 mm ± 1.52) (p<0.005) and S pyogenes ( 15.6 mm ±1.15) (p<0.005). Similar pattern of the inhibition grow1h was observed among the wild-type strains [S. aureus (29.3 mm ±0.57) (p<0.005). S. epidermidis (E6 mm ±1.52) (p<0.005). S. pneumoniae (11.3 mm ±1.52) (p<0.005) and S. pyogenes (15.6 mm ±1.15) (p<0.005)]. None of the extracts were active against fungus (Candida .1pp.). The minimum inhibitory concentration (MlC) of the n-hcxane extract was 100 mg/ml against S. aureus and 50 mg/ml against S. epidermidis. S. pneumoniae and S. pyogenes respectively. The GC-MS analysis indicated decanal. caryophyllene. dodecanal as the major constituents of then-hexane extract. In conclusion. P. odora/a have antibacterial property especially to some important Gram-positive pathogens. Further studies are worth to be carried out to evaluate the potential of this plant as the antibacterial agent.